ISTILAH KHAS DALAM SENI TARI KLASIK YOGYAKARTA - Tri Ana Ratnasari; Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2016)
The aim of this research is to describe (1) the specific term in Yogyakarta classic dance and (2) the difference meaning between a specific term in Yogyakarta classic dance and general term. This research is a qualitative research. The data of the research are words sentences which contain specific terms in Yogyakarta classic dance. The data sources are the use of language in Ndalem Pujokusuman classic dance studio Yogyakarta and there is some written resource from books such as Bedhaya Suryasumirat by Suharji (2004), internet, Suprihono book (1994/1995), Istilah Tari dan Karawitan Jawa Dictionary written by Sudarsono, B. Suharto, Y. Sumandyo Hadi, et el (1978), and Bahasa Jawa Dictionary (Bausastra Jawa) by the team of Balai Â Bahasa Yogyakarta 2011. The collecting data method and technic in this research is using simak method with the simak libat cakap method, noting method, record method, cakap method with cakap semuka technic and rekam and catat technic. Data analysis method and technic in this research is a padan method with referential technic and translational technic. The serving data analysis result in this research is informal method. The research result show what: (1) the term use in Yogyakarta classic dance contain of base term and relegated term that cover the term which is formed by the affixation processes, the term that is form by the reduplication processes, and the term which is formed by the processes of compand and (2) there ar differences of meaning in the term that is used in Yogyakarta classic dance with the meaning of general term that is found in Basa Jawa Dictionary (Bausastra Jawa).